2016
DOI: 10.1097/ico.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Posterior Corneal Astigmatism on Total Corneal Astigmatism in Eyes With Keratoconus

Abstract: In eyes with keratoconus, PCA displays large, variable values and is correlated to TCA. The influence of PCA on TCA cannot be disregarded when planning astigmatism correction by toric intraocular lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
3
21
2
2
Order By: Relevance
“…The mean power values for posterior astigmatism as reported by Ho et al [11], Koch et al [12], and Zhang et al [25] are 0.30 D, 0.30 ± 0.15 D, and 0.33 ± 0.16 D, respectively. In eyes with keratoconus, the posterior corneal astigmatism displays large and variable values for total corneal astigmatism [26]. Anterior corneal astigmatism and posterior corneal astigmatism were 4.47 ± 2.05 diopters and 0.87 ± 0.44 diopters in the present study.…”
Section: Discussionsupporting
confidence: 39%
“…The mean power values for posterior astigmatism as reported by Ho et al [11], Koch et al [12], and Zhang et al [25] are 0.30 D, 0.30 ± 0.15 D, and 0.33 ± 0.16 D, respectively. In eyes with keratoconus, the posterior corneal astigmatism displays large and variable values for total corneal astigmatism [26]. Anterior corneal astigmatism and posterior corneal astigmatism were 4.47 ± 2.05 diopters and 0.87 ± 0.44 diopters in the present study.…”
Section: Discussionsupporting
confidence: 39%
“…As a result, in 90.9% of eyes with keratoconus, the flat meridian difference between the anterior corneal surface and the total cornea was less than or equal to 10 degrees. In line with this study, Savini et al [ 18 ] demonstrated that eyes with keratoconus showed a tendency for the steep meridians of the anterior and posterior corneal surfaces to be aligned regardless of the type of astigmatism (WTR, ATR, or oblique astigmatism). In that study, the steep meridian difference between the anterior corneal surface and the total cornea was greater than 10 degrees in only 8.4% of eyes with keratoconus [ 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…[5][6][7] This may be due to the unsynchronized changes of the ACA and PCA during the development of keratoconus, and the tendency towards a better alignment of the PCA to the ACA in keratoconus eyes. [16][17][18] In the present study, there were weak correlations (R: 0.29 to 0.45) between the anterior and posterior corneal asphericity in all the quantile groups. These ndings were different from previous studies where poor anteriorposterior corneal asphericity correlations in normal eyes 1,5 and good correlations in keratoconus eyes were observed.…”
Section: Discussioncontrasting
confidence: 67%